The Global Productivity Slowdown: Diagnosis, Causes and Remedies - Georg Erber; Ulrich Fritsche; Patrick Christian Harms (Intereconomics, 2017)
This paper addresses the long-term slowdown in labour productivity for a panel of 25 countries. First, we look at productivity shifts and trends based on structural break tests and modern filtering techniques. The productivity slowdown is evident in almost all countries we investigate. Second, we deepen the analysis by decomposing labour productivity growth. Third, we use dynamic models to test for Granger causality in the trends and find that there is strong evidence that a slow GDP growth trend causes the subsequent productivity trend. We conclude that the productivity slowdown is a global phenomenon and should therefore be tackled at the international level.
Keywords: 330